Otherworlds, doubles, houses : Helen Oyeyemi’s The Opposite House and White Is for Witching - Anita Harris Satkunananthan (Penerbit Universiti Kebangsaan Malaysia, 2018)
Houses feature prominently in Helen Oyeyemi’s novels, The Opposite House and White Is for Witching. I describe the connection between the Greco-Roman Underworld and the Yorùbá Otherworld in Oyeyemi’s texts as a “liminal intersection”, one in which Gothic and supernatural metaphors from the Yorùbá culture are syncretised. The Gothic tropes of the House collide with Oyeyemi’s revisioning of the Yorùbá pantheon and Otherworld. Key figures and symbols from Greco-Roman folklore, Yorùbá mythology and European fairytales are either represented by characters in Oyeyemi’s novels or are present as metaphors. The problematic postcolonial Gothic relationship between competing cultural imperatives and authorities in The Opposite House and White is For Witching takes place in these liminal intersections. I connect this struggle to the idea of transgression as agency. Pursuant to this, this article interrogates the postcolonial Gothic house as a trope in the two studied texts and argues that it is a site for the enactment of liminal and hybrid transgressions as agency through the deployment of the metaphors of doubling and that of the temporal slippage between multiple realities and the findings elucidate the ways in which the House as a gateway to the Otherworld may be a site for empowerment and decolonising through transgression.